Visualisasi Heroik Makhluk Mitologi: Analisis Ilustrasi Desain Karakter Genderuwo Penjaga Mata Air Desa Ngrundul - Fatikha Dahayuna Qaulansadida (VisArt: Jurnal Seni Rupa dan Design, 2026)
The availability of clean water in Ngrundu, Klaten faces a decline in ecological awareness due to the water spring preservation myths. Conventional perspectives mistakenly identify Genderuwo as a destructive horror figure, thereby eroding the conservation values behind gayam trees as natural water binders. This study aims to produce a radical visual reconstruction of Genderuwo as a Water Spring Protector into a heroic figure through digital illustration. The method used is descriptive qualitative based on practice-based research. The design results manifest in a fictional character named "Ruwo" with an ideal warrior body proportion (1:8), dominant stable geometric shapes, traditional Klaten lurik fabric, hair textured with gayam root, and an emerald green color palette. The conclusion shows that aesthetic modifications of colored manga style can shift the audience's paradigm from terror to empathy and admiration. The benefit of this research provides a scientific contribution in the form of an admiration-centric conservation approach model as well as a visual prototype that elevates the status of local mythological creatures to the international creative industry stage